Traditional vs. Modern Human Resource Management: Typology, Transformation, and Industry 4.0 Implications - Meutia Dwi Novita Sari; Raisa Ullya Nisva; M. Rizki Maulana (PT FORMOSA CENDEKIA GLOBAL, 2025)
For more than three decades, human resource management (HRM) has evolved from an administrative function geared toward payroll, compliance, and record keeping into a strategic, evidence-based capability that shapes organizational performance and long-term competitiveness. This paper examines the differences between traditional and modern HRM, the field’s development, and transformation mechanisms in the Digital/Industry 4.0 era. This study adopts a qualitative, descriptive approach. Core concepts include HRM logics, e-HRM/HRIS and people analytics, and Industry 4.0. We propose a four-dimension typology (value logic, operating model, data/technology, metrics/decision rights) and a staged pathway (digitalization → standardization → analytics → strategic partnering). Enablers are data governance, analytics capability, and HR–business partnership; a key risk is technology without process redesign. Implications guide organizations and policymakers on sequencing, ethics, and outcome-based metrics.